Pathways Implicated in Tadalafil Amelioration of Duchenne Muscular Dystrophy. Issue 1 (January 2016) - De Arcangelis, Valeria; Strimpakos, Georgios; Gabanella, Francesca; Corbi, Nicoletta; Luvisetto, Siro; Magrelli, Armando; Onori, Annalisa; Passananti, Claudio; Pisani, Cinzia; Rome, Sophie; Severini, Cinzia; Naro, Fabio; et al.
<x xml:space="preserve">Abstract</x> Numerous therapeutic approaches for Duchenne and Becker Muscular Dystrophy (DMD and BMD), the most common X‐linked muscle degenerative disease, have been proposed. So far, the only one showing a clear beneficial effect is the use of corticosteroids. Recent evidence indicates an improvement of dystrophic cardiac and skeletal muscles in the presence of sustained cGMP levels secondary to a blocking of their degradation by phosphodiesterase five (PDE5). Due to these data, we performed a study to investigate the effect of the specific PDE5 inhibitor, tadalafil, on dystrophic skeletal muscle function. Chronic pharmacological treatment with tadalafil has been carried out in mdx mice. Behavioral and physiological tests, as well as histological and biochemical analyses, confirmed the efficacy of the therapy. We then performed a microarray‐based genomic analysis to assess the pattern of gene expression in muscle samples obtained from the different cohorts of animals treated with tadalafil. This scrutiny allowed us to identify several classes of modulated genes. Our results show that PDE5 inhibition can ameliorate dystrophy by acting at different levels. Tadalafil can lead to (1) increased lipid metabolism; (2) a switch towards slow oxidative fibers driven by the up‐regulation of PGC‐1α; (3) an increased protein synthesis efficiency; (4) a better actin network organization at Z‐disk. J. Cell. Physiol. 230: 224–232, 2016. © 2015 Wiley Periodicals, Inc.